2017
DOI: 10.1073/pnas.1619735114
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytopathic factors through genome-wide analysis of the Zika viral proteins in fission yeast

Abstract: The Zika virus (ZIKV) causes microcephaly and the Guillain-Barré syndrome. Little is known about how ZIKV causes these conditions or which ZIKV viral protein(s) is responsible for the associated ZIKVinduced cytopathic effects, including cell hypertrophy, growth restriction, cell-cycle dysregulation, and cell death. We used fission yeast for the rapid, global functional analysis of the ZIKV genome. All 14 proteins or small peptides were produced under an inducible promoter, and we measured the intracellular loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 89 publications
3
99
0
Order By: Relevance
“…A mechanistic study revealed that NS4A-induced cellular hypertrophy and growth restriction were mediated specifically through the target of rapamycin (TOR) cellular stress pathway involving Tor1 and type 2A phosphatase activator Tip41. 191 Moreover, the appearance of neurologic syndromes associated with ZIKV could be related to the persistence of the virus, which can persist for a substantially long period, likely as a result of activation of mTOR, proinflammatory, and anti-apoptotic pathways that promote survival of infected cells, as well as exclusion of virusspecific antibodies from CSF. If persistent or occult neurologic and lymphoid disease similarly occurs following clearance of peripheral virus in ZIKV-infected humans, such a finding would have important clinical implications.…”
Section: Chikungunya Virus and Gbsmentioning
confidence: 99%
“…A mechanistic study revealed that NS4A-induced cellular hypertrophy and growth restriction were mediated specifically through the target of rapamycin (TOR) cellular stress pathway involving Tor1 and type 2A phosphatase activator Tip41. 191 Moreover, the appearance of neurologic syndromes associated with ZIKV could be related to the persistence of the virus, which can persist for a substantially long period, likely as a result of activation of mTOR, proinflammatory, and anti-apoptotic pathways that promote survival of infected cells, as well as exclusion of virusspecific antibodies from CSF. If persistent or occult neurologic and lymphoid disease similarly occurs following clearance of peripheral virus in ZIKV-infected humans, such a finding would have important clinical implications.…”
Section: Chikungunya Virus and Gbsmentioning
confidence: 99%
“…NS4A and NS4B deregulate Akt-mTOR signaling to inhibit neurogenesis and induce autophagy ( Liang et al, 2016 ). In addition, the expression of NS4A has been also related to activation of the cellular stress pathway involving Tor1 and type 2A phosphatase activator Tip41 ( Li G. et al, 2017 ). NS5 is the viral RNA-dependent RNA polymerase that is in charge of genome replication constituting a major target for antiviral design ( Lu et al, 2017 ; Xu et al, 2017 ).…”
Section: Biology Of the Zikvmentioning
confidence: 99%
“…In a recent study using a fission yeast cell system, it has been shown that all ZIKV structural proteins, with the exception of Pr and two non-structural proteins (NS2B and NS4A), conferred cytopathic effects that included inhibition of growth/ proliferation, cell hypertrophy, cellcycle dysregulation, and cell death [60]. Genetic studies suggested that cellular hypertrophy and growth restriction were mediated through the Tor1 and Tip41 proteins of the TOR cellular stress-response pathway [60].…”
Section: Targeting Tor Stress-response Pathwaymentioning
confidence: 99%
“…Genetic studies suggested that cellular hypertrophy and growth restriction were mediated through the Tor1 and Tip41 proteins of the TOR cellular stress-response pathway [60].…”
Section: Targeting Tor Stress-response Pathwaymentioning
confidence: 99%